2010
DOI: 10.1177/0032885510363387
|View full text |Cite
|
Sign up to set email alerts
|

Would They Officially Report an In-Prison Sexual Assault? An Examination of Inmate Perceptions

Abstract: This exploratory study examined inmates' intentions to report their own sexual victimization and recommend others to officially report their assaults. More than 900 male and female inmates in a Southern prison system responded to the self-report questionnaire. Victims of prison sexual assault and homosexual/bisexual inmates, at risk for victimization, had decreased chances of reporting their own victimization. As inmates' time served increased their chances of intending to report their victimization decreased.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 49 publications
(63 reference statements)
0
31
0
Order By: Relevance
“…Women of color (specifically African American and Latina women) who are victims are less likely to report rape than White women (Bryant-Davis, Chung, Tillman, & Belcourt, 2009) due to multiple barriers such as racist stereotypes about African American women's sexuality (Tillman et al, 2010). Other community-based studies have found that women of color were more likely to report sexual victimization (Bachman, 1998;Chen & Ullman, 2010;Fisher et al, 2003), and this was also found in one prison-based study using hypothetical situations (Fowler et al, 2010).…”
Section: Reporting Sexual Assault In Prisons: Influencing Factors Acrmentioning
confidence: 81%
“…Women of color (specifically African American and Latina women) who are victims are less likely to report rape than White women (Bryant-Davis, Chung, Tillman, & Belcourt, 2009) due to multiple barriers such as racist stereotypes about African American women's sexuality (Tillman et al, 2010). Other community-based studies have found that women of color were more likely to report sexual victimization (Bachman, 1998;Chen & Ullman, 2010;Fisher et al, 2003), and this was also found in one prison-based study using hypothetical situations (Fowler et al, 2010).…”
Section: Reporting Sexual Assault In Prisons: Influencing Factors Acrmentioning
confidence: 81%
“…When inmate‐on‐inmate sexual assaults do come to the attention of authorities, according to Guerino and Beck (2011), approximately 70.0 percent of it is the result of the victim reporting. Fowler et al (2010) found that 62.3 percent of inmates indicated they would definitely report it if they were sexually assaulted by another inmate. Outside prison, according to the National Crime Victimization Survey, 31.0 percent of sexual assaults and 55.0 percent of physical assaults are reported to the police (Hart and Rennison, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…We have four reasons to think that the underreporting bias does not undermine our conclusions. First, Fowler et al (2010) found that age was not significantly related to whether inmates said they would report sexual assault victimization to authorities. Second, results from a study outside prison found that the victim's age has a weak positive relationship to victim reporting of sexual and physical assault to the police, and that it is unrelated to third‐party reporting (Felson and Paré, 2005).…”
Section: Limitationsmentioning
confidence: 97%
“…Some studies have focused on exploring inmate prison life (Crank, 2010), while others examined the advantages and disadvantages of prison relative to probation (Crouch, 1993). Several authors have also explored correctional officer job competency (Boyd and Grant, 2005; Cheeseman and Worley, 2006), as well as differences in perceptions of sanction severity as related to the racial background of the inmates (Wood and May, 2003) and the crimes they committed (Blackburn, 2006; Fowler, Blackburn, Marquart and Mullings, 2010; Connor, 2009). However, inmates’ perceptions of the criminal process (specifically the legal defence) have rarely been examined.…”
Section: Methodsmentioning
confidence: 99%